2016
DOI: 10.1371/journal.pone.0165920
|View full text |Cite
|
Sign up to set email alerts
|

Viability-PCR Shows That NAAT Detects a High Proportion of DNA from Non-Viable Chlamydia trachomatis

Abstract: ObjectivesAccording to the current guidelines for laboratory diagnosis of sexually transmitted infections (STIs), nucleic acid amplification tests (NAATs) are the preferred diagnostic method for Chlamydia trachomatis (CT) infections. However, NAATs amplify the available target DNA without discriminating between DNA originating from viable or non-viable CT. Assessing CT viability will provide more insights in the clinical and public health relevance of a CT positive test result. The aim of this study was to tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 30 publications
6
44
0
1
Order By: Relevance
“…Our finding of approximately 20% mRNA negative is similar to those of Janssen and colleagues [17] who developed a viability PCR (V-PCR) assay to assess CT viability and found that 24% of vaginal swabs from women diagnosed CT PCR positive had non-viable DNA only. Unlike our assay which quantified mRNA as a marker of viable CT, their V-PCR assay consisted of propidium monoazide (PMA) treatment prior to DNA extraction followed by quantitative PCR targeting the ompA gene for the detection of CT DNA.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding of approximately 20% mRNA negative is similar to those of Janssen and colleagues [17] who developed a viability PCR (V-PCR) assay to assess CT viability and found that 24% of vaginal swabs from women diagnosed CT PCR positive had non-viable DNA only. Unlike our assay which quantified mRNA as a marker of viable CT, their V-PCR assay consisted of propidium monoazide (PMA) treatment prior to DNA extraction followed by quantitative PCR targeting the ompA gene for the detection of CT DNA.…”
Section: Discussionsupporting
confidence: 88%
“…The evaluation of CT viability in rectal samples by V-PCR is feasible and valid. Previously, we validated the V-PCR method in vaginal samples from women 12. In the current study, CT culture has been conducted as a validation approximation of CT viability for V-PCR and showed that samples with no evidence for viable CT or samples with an unquantifiable total load were also negative for CT culture.…”
Section: Discussionmentioning
confidence: 70%
“…Assessment of CT viability was achieved by using the V-PCR method as described previously with minor adaptions12: in the current study, propidium monoazide (PMA) photoactivation was completed by using the PMA-Lite LED Photolysis Device (Biotium, Hayward, California, USA) with an exposure time of 10 min. Furthermore, CT quantification was conducted in a total volume of 50 µL to achieve a higher sensitivity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations